2012
DOI: 10.1080/13549839.2011.646966
|View full text |Cite
|
Sign up to set email alerts
|

Wind power! Marketing renewable energy on tribal lands and the struggle for just sustainability

Abstract: Using a case study approach and employing the critical framework of just sustainability, this article examines the ambivalent intersections of marketing and social/environmental justice as articulated through the public rhetoric of corporate entities that promote renewable energy generated on American Indian tribal lands. Because of its critical interest in the empowerment of disenfranchised communities through a shift away from traditional ways of valuing environmental sustainability and economic activity, ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Attention has also turned to the impacts of the conventional food production system on farm laborers and their families (Dorward, 2013;Fridell, 2007;Wilson & Curnow, 2013) and on rural communities globally (Crowell & Sligh, 2006;Meléndez-Ortiz, 2011;Wilkinson, 2009;Varul, 2008). Others have focused on gender and ethnic disparities in both natural resource conservation and destruction (Brady & Monani, 2012;Hecht, 2007;Robinson, 2011). There is an emerging consensus among these researchers that deeply embedded social and economic structures create and propagate these disparities, that these structures are globally systemic, and that the traditional emphases on environmental and economics in sustainable agriculture will not address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Attention has also turned to the impacts of the conventional food production system on farm laborers and their families (Dorward, 2013;Fridell, 2007;Wilson & Curnow, 2013) and on rural communities globally (Crowell & Sligh, 2006;Meléndez-Ortiz, 2011;Wilkinson, 2009;Varul, 2008). Others have focused on gender and ethnic disparities in both natural resource conservation and destruction (Brady & Monani, 2012;Hecht, 2007;Robinson, 2011). There is an emerging consensus among these researchers that deeply embedded social and economic structures create and propagate these disparities, that these structures are globally systemic, and that the traditional emphases on environmental and economics in sustainable agriculture will not address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…The energy justice literature notes that any inequitable distribution of benefits and outcomes of renewable energy projects may also create conflicts and resentment within the communities hosting those projects (Brady and Monani, 2012;Gross, 2007;Walker and Devine-Wright, 2008). Echoing this, various interviewees' accounts emphasised the inequitable distribution of economic opportunities within the village.…”
Section: Local Economic Development Opportunitiesmentioning
confidence: 95%
“…Wind and solar energy were the two most common renewable energy technologies that appeared throughout the review at 7 (27%) and 5 (19%) records, respectively, while energy derived from hydroelectricity and tidal power were discussed in 2 records (8% (Brady & Monani 2012), and the destruction of ecosystems that results from large-scale hydroelectric dams (Cizek 2004).…”
Section: Characteristics Of Research Studiesmentioning
confidence: 99%
“…As an overall goal of renewable energy initiatives, Indigenous peoples cited forms of autonomy -be it within environmental, economic, or socio-political contexts -as a primary driver in motivating a Reviewed literature suggested that reconciliation and healing often occur through a balancing of goals related to ecological sustainability and economic prosperity. Brady and Monani (2012) posit that viewing Indigenous peoples through a binary lens of "The Ecological Indian" who is opposed to all development, versus a narrow focus only on economic prosperity and development at any costs is both overly reductionist, and likely impedes the implementation of renewable energy initiatives in Indigenous territories. Coates 2016 Indigenous leaders and community actors in roles with decision-making power, the likelihood of community dissent and unrealistic expectations for the project -goals that may ultimately not be achieved -increases significantly (Krupa et al 2015).…”
Section: Research Outcomes: the Drivers Of Renewable Energy Initiativesmentioning
confidence: 99%